ANALYSIS OF CAPITAL ASSET PRICING MODEL (CAPM) ON HEALTH SECTOR STOCKS AS A GROWING SECTOR DURING THE PANDEMIC - Muhammad Iffadel Rasyad (Econosains Jurnal Online Ekonomi dan Pendidikan, 2022)
Covid-19 pandemic has changed people's behavior, from initially spending a lot of money to being more active in saving. This pandemic has also increased public interest in investing in line with the desire for financial well-being. Based on KSEI data, this increase in the number of investors is six times higher than at the end of 2017. Capital Asset Pricing Model (CAPM) is a model that can be used to see the expected return in a balanced market. The main objective of CAPM is to assist investors in making optimal stock choices while avoiding risk. This study aims to examine CAPM approach in making investment choices in the health sector. This study uses a quantitative descriptive method. The data used in this study is secondary data in the form of financial reports of health sector companies listed on Indonesia Stock Exchange for the period March 2020 to February 2022. Based on the research results, 18 health sector stocks have a positive average return, 17 stocks are included in the category of efficient stock, and 1 stock is included in the category of inefficient stock. When the stock return exceeds the expected rate of return, then the stock is considered efficient.